Neighborhood environment: the impact of alcohol and tobacco outlets availability on health of people living in a certain area - A. A. Antsiferova; A. V. Kontsevaya; D. K. Mukaneeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Alcohol and tobacco consumption remain significant risk factors (RFs) for morbidity and mortality from noncommunicable diseases (NCDs), including cardiovascular ones, in Russia. The main risk factors contributing to NCDs in addition to traditional risk factors and lifestyle also include the neighborhood environment (NE). The term “neighborhood environment” describes the relationship between the area in immediate vicinity of a person's place of residence, environmental factors, social characteristics of the area, which can have both positive and negative effects on human health.The aim of this review was to analyze alcohol and tobacco outlets availability as a factor effecting health of people living in a certain area.It was demonstrated that a high density of alcohol outlets is associated with increased alcohol consumption among both adults and adolescents, with drunk driving and road traffic accidents, injuries, violent crimes, the risk of acute and chronic diseases. A high density of tobacco outlets is associated with an increase in smoking intensity among both adults and adolescents, as well as an increase of secondhand smoke, which increases the risk of NCDs.The consumption of alcohol and tobacco is associated with a significant increase in risk of NCDs, including cardiovascular ones, and injuries, leading to disability and death. The effectiveness of measures aimed at reducing the consumption of alcohol and tobacco may be reduced due to high density of outlets selling these products. It is necessary to conduct studies aimed at assessing the outlets density and its associations with prevalence of RFs and health status of Russian population. These data will stimulate intersectoral collaboration for planning health protection strategy at municipal level.